P-95 SARCOPENIA: RISK FACTOR FOR MORTALITY IN CIRRHOTIC PATIENTS ON WAITING LIST FOR LIVER TRANSPLANTATION IN A REFERENCE CENTER, COLOMBIA - Gustavo Andres Diaz Nassif; Geovanny Hernandez Cely (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Sarcopenia is an independent predictor of mortality in patients with chronic liver disease pre- and post-transplant. Measurement of muscle strength by dynamometry can serve as a surrogate marker of frailty in patients with chronic liver disease, especially in those in whom it is not possible to assess sarcopenia through imaging. Patients / Materials and Methods: To determine the association between sarcopenia, complications of cirrhosis and mortality in cirrhotic patients on the waiting list for liver transplant in a liver transplant reference center in Colombia. Methods: An observational, analytical and retrospective study was carried out with a cohort of patients with cirrhosis on the waiting list for liver transplant between 2020 and 2022, in a liver transplant reference center in Colombia. Results and Discussion: We included 310 patients with a diagnosis of cirrhosis who were on the liver transplant waiting list and had dynamometry and anthropometry records to calculate the SARC-F index. A bivariate analysis was carried out which shows that a high score in CHILDA, MELD, ICU stay, complications such as SBP, dynamometry measurement and sarcopenia generate an estimate of significant association, taking into account a p <0.05. Subsequently, a multinomial logistic regression model was carried out, chronic kidney disease and sarcopenia stand out as influential factors in mortality with P <0.05. Conclusions: Sarcopenia and chronic kidney disease are factors that have a significant association with higher mortality.